Autoimmune Thrombotic Microangiopathy: Advances in Pathogenesis, Diagnosis, and Management - Tsai, Han-Mou (Seminars in Thrombosis and Hemostasis, 2012)
Thrombotic microangiopathy, or the syndrome of thrombocytopenia and hemolysis with schistocytes on blood smears, has been a subject of uncertainty and intense controversy. The pathogenesis of thrombotic microangiopathy was unknown and no classification of thrombotic thrombocytopenic purpura and hemolytic uremic syndrome was satisfactory. In recent years, a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13 (ADAMTS-13) deficiency and defective complement regulation have been identified as the two major causes of noninfectious thrombotic microangiopathy. It is now possible to classify thrombotic microangiopathy pathogenetically rather than clinically, and a distinction between diseases and clinical syndromes is emerging. This pathogenesis-based disease classification requires new diagnostic approaches and provides a framework for rational therapeutic designs. This review discusses the new concepts in the pathogenesis, diagnosis, and management of thrombotic microangiopathy, with particular emphasis on the autoimmune causes of ADAMTS-13 deficiency and defective complement regulation.
Keywords: thrombotic thrombocytopenic purpura; hemolytic uremic syndrome; thrombotic microangiopathy; autoimmunity; ADAMTS-13